2017
DOI: 10.1038/s41598-017-16909-x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing biomass recalcitrance by heterologous expression of a bacterial peroxidase in tobacco (Nicotiana benthamiana)

Abstract: Commercial scale production of biofuels from lignocellulosic feed stocks has been hampered by the resistance of plant cell walls to enzymatic conversion, primarily owing to lignin. This study investigated whether DypB, the lignin-degrading peroxidase from Rodococcus jostii, depolymerizes lignin and reduces recalcitrance in transgenic tobacco (Nicotiana benthamiana). The protein was targeted to the cytosol or the ER using ER-targeting and retention signal peptides. For each construct, five independent transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 134 publications
(198 reference statements)
0
11
0
Order By: Relevance
“…Leaf explants (~0.5 mm 2 ) of 4–6-week-old tobacco were infiltrated with Agrobacterium harboring the expression vectors pPZP- NPTII - Cg1 , pPZP- NPTII - glgC , and pPZP- NPTII - Cg1-glgC or the empty vector pPZP-NPTII for five minutes in the presence of 200 μ M acetosyringone. Handling of transformed tissues, selection and regeneration, and maintenance of transgenic lines were performed based on Ligaba-Osena et al [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaf explants (~0.5 mm 2 ) of 4–6-week-old tobacco were infiltrated with Agrobacterium harboring the expression vectors pPZP- NPTII - Cg1 , pPZP- NPTII - glgC , and pPZP- NPTII - Cg1-glgC or the empty vector pPZP-NPTII for five minutes in the presence of 200 μ M acetosyringone. Handling of transformed tissues, selection and regeneration, and maintenance of transgenic lines were performed based on Ligaba-Osena et al [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Expression of transgenes ( Cg1 and glgC ) and putative Cg1 -targets was studied by quantitative real-time RT-PCR (qPCR) as described previously [ 39 ]. Primers used for gene expression analysis are listed in Table S1 ; 18S RNA was used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In model studies, oxidative cleavage by Dyp-type peroxidases has only been observed using units containing a free phenolic 4-hydroxyl group [6], therefore it seems likely that for breakdown of polymeric lignin breakdown, they cleave from the ends of a lignin chain (exo-cleavage), rather than in the middle of a chain (endo-cleavage). Expression of R. jostii DypB in tobacco plants has been shown to yield 200% more fermentable sugars, and reduced lignin content, demonstrating that Dyp-type peroxidases can be expressed heterologously to depolymerise lignin [39].…”
Section: Biotransformation Of Lignin By Lignin-depolymerising Enzymesmentioning
confidence: 99%
“…Therefore, utilization of renewable materials becomes an encouraging way to resolve the problem to maintain the sustainable development of human beings [2]. As the second-most-abundant biomass resource on Earth, after cellulose, lignin is a natural renewable resource with great potential [3,4]. Its chemical structure is complex [5] and its chemical composition varies with irregular arrays, resulting in valuable physicochemical properties [6,7].…”
Section: Introductionmentioning
confidence: 99%